2018
DOI: 10.1111/cmi.12854
|View full text |Cite
|
Sign up to set email alerts
|

Actin‐based motility allows Listeria monocytogenes to avoid autophagy in the macrophage cytosol

Abstract: Listeria monocytogenes grows in the host cytosol and uses the surface protein ActA to promote actin polymerisation and mediate actin-based motility. ActA, along with two secreted bacterial phospholipases C, also mediates avoidance from autophagy, a degradative process that targets intracellular microbes. Although it is known that ActA prevents autophagic recognition of L. monocytogenes in epithelial cells by masking the bacterial surface with host factors, the relative roles of actin polymerisation and actin-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 59 publications
0
38
0
Order By: Relevance
“…OmpB appears to act differently from other pathogen proteins that protect against polyubiquitylation. Form example, the L.monocytogenes surface protein ActA blocks polyubiquitylation by mobilizing the host actin machinery to the bacterial surface, which is required to protect the bacterium from autophagic recognition 11,25,51 . In contrast, OmpB has no effect on host actin mobilization by R. parkeri.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OmpB appears to act differently from other pathogen proteins that protect against polyubiquitylation. Form example, the L.monocytogenes surface protein ActA blocks polyubiquitylation by mobilizing the host actin machinery to the bacterial surface, which is required to protect the bacterium from autophagic recognition 11,25,51 . In contrast, OmpB has no effect on host actin mobilization by R. parkeri.…”
Section: Discussionmentioning
confidence: 99%
“…Several facultative intracellular bacterial pathogens that grow in the host cell cytosol have evolved mechanisms to evade autophagic recognition 9,21,22,23,24 . For example, Listeria monocytogenes uses its surface protein ActA to avoid polyubiquitin coat formation by masking the bacterial surface with components of the host actin machinery 22 and inducing actin polymerization and intracellular motility 11,25 . It remains unclear whether or how other pathogens avoid polyubiquitin coat formation, and what microbial proteins are ubiquitylated by the host.…”
Section: Introductionmentioning
confidence: 99%
“…ActA facilitates aggregation in L. monocytogenes through uninterrupted ActA-ActA interactions, is involved in biofilm formation, and mediates intestinal colonization [47]. Results from one study demonstrated that actin-based intracellular motility facilitates the exit of the pathogen from autophagic membranes within the macrophage cytosol [48].…”
Section: Actamentioning
confidence: 99%
“…LLO is necessary to escape from both a primary phagosome and the secondary vacuole that forms upon cell‐to‐cell spread. LLO‐damaged phagosomes and free bacteria in the cytosol are recognised by the host autophagy machinery, but the bacteria secrete two phospholipases C (PlcA/B), and utilise actin‐based motility, that together allow them to bypass autophagy (Cheng, Chen, Engstrom, Portnoy, & Mitchell, ; Mitchell et al, ). Importantly, mutants lacking LLO are incapable of growth in BMMs and are 5‐logs less virulent in mice (Portnoy, Jacks, & Hinrichs, ).…”
Section: Cell Biology Of Infectionmentioning
confidence: 99%